Clinical Application of Modern Dental Pins And Their Classification - Hojimurodov Burkhon Ravshanovich (Academia One Publishing, 2023)
to systematize knowledge about dental pins used to restore the morpho functional integrity of the tooth - the structural unit of the alveolar bone system.
Keywords: tooth; systematize; system